Latar Belakang Munculnya Kutukan dalam Cerita Rakyat di Jawa - Suratno, Pardi; Nugroho, Yusro Edi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2022)
Literary works, including folklore, reflect the thoughts of the people who support them. Stories containing curses are also expressions of the supporting community. This study attempts to reveal the background of the emergence of curses in several folklore in Java. Second, it reveals the dominance of the background for the emergence of the curse in Java. Third, to describe the dominance of the emergence of curses in folklore in West Java, Central Java, East Java and Yogyakarta. This study departs from the background problem of what underlies the emergence of curses in Javanese folklore. The method used is a qualitative description method with careful and thorough reading and recording. The result of this study is a description of the background of the emergence of curses in folklore, related to family, moral, social, and political problems. The conclusion that can be formulated is that the presence of curses in Javanese folklore is motivated by family, social, moral or ethical, and political issues.